The posteromedial corner of the knee: an international expert consensus statement on diagnosis, classification, treatment, and rehabilitation - Chahla, Jorge; Kunze, Kyle N; LaPrade, Robert F; Getgood, Alan; Cohen, Moises; Gelber, Pablo; Barenius, Björn; Pujol, Nicolas; Leyes, Manual; Akoto, Ralph; Fritsch, Brett; Margheritini, Fabrizio; et al. (Knee surgery, sports traumatology, arthroscopy, 2021)
PURPOSE: To establish recommendations for diagnosis, classification, treatment, and rehabilitation of posteromedial corner (PMC) knee injuries using a modified Delphi technique. METHODS: A list of statements concerning the diagnosis, classification, treatment and rehabilitation of PMC injuries was created by a working group of four individuals. Using a modified Delphi technique, a group of 35 surgeons with expertise in PMC injuries was surveyed, on three occasions, to establish consensus on the inclusion or exclusion of each statement. Experts were encouraged to propose further suggestions or modifications following each round. Pre-defined criteria were used to refine item lists after each survey. The final document included statements reaching consensus in round three. RESULTS: Thirty-five experts had a 100% response rate for all three rounds. A total of 53 items achieved over 75% consensus. The overall rate of consensus was 82.8%. Statements pertaining to PMC reconstruction and those regarding the treatment of combined cruciate and PMC injuries reached 100% consensus. Consensus was reached for 85.7% of the statements on anatomy of the PMC, 90% for those relating to diagnosis, 70% relating to classification, 64.3% relating to the treatment of isolated PMC injuries, and 83.3% relating to rehabilitation after PMC reconstruction. CONCLUSION: A modified Delphi technique was applied to generate an expert consensus statement concerning the diagnosis, classification, treatment, and rehabilitation practices for PMC injuries of the knee with high levels of expert agreement. Though the majority of statements pertaining to anatomy, diagnosis, and rehabilitation reached consensus, there remains inconsistency as to the optimal approach to treating isolated PMC injuries. Additionally, there is a need for improved PMC injury classification. LEVEL OF EVIDENCE: Level V.
Keywords: Knee Injuries; Medial collateral ligament; Knee; lidé; Consensus; poranění kolena; Diagnosis; Posteromedial corner; Treatment; konsensus; kolenní kloub; Knee Joint; Humans; Delphi